A comparison of clinical profile and treatment outcome of Hodgkin’s Lymphoma in Tanzania according to HIV status during the HAART era - Mercy M. Mbai; Emmanuel Mduma; Samuel Thuo; Eulade Rugengamanzi; Christina V. Malichewe; Emmanuel L. Lugina (BMC Cancer, 2024)
Abstract Background The incidence of Hodgkin's lymphoma (HL) in people living with HIV (PLWHA) and on HAART is approximately 20–30 times higher than in HIV-negative individuals. Most patients with HIV-HL present at an advanced stage (III-IV) have 'B' symptoms and extranodal involvement. The natural history and risk stratification of HIV-HL has undergone a significant change as a result of HAART's rollout. This study investigated the differences in clinicopathological and survival patterns of HL among individuals with and without HIV disease in Tanzania during the HAART era. Methodology This hospital-based retrospective cohort study was conducted at the ORCI, Dar-Es-Salaam, Tanzania. Chi-square and Fisher’s exact tests were used to compare proportions. The student t-test was used to compare means. To determine factors that predict survival, we used the log-rank test to analyze the variables in univariate analysis. A Cox regression model was used to analyze the significant factors from univariate analysis in multivariate analysis. Results Eighty-three patients with HL were recruited, and the prevalence of HIV-positive status was 27.7%. Most of the patients with HIV-HL had an age of > 30 years (73.9%), while most of the non-HIV-HL patients had an age of ≤ 30 years (63.3%) (P = 0.02). The 2-year OS rate for HIV-HL was 34%, while that for non-HIV-HL was 67%. Among the HIV-HL patients, predictors of a poorer outcome were a CD4 count ≤ 200 cells/mm3 (P = 0.05), lack of HAART use (P = 0.00), and the use of HAART for ≤ 10 months (P = 0.00). Conclusion The prevalence of HIV-HL was 27.7% among HL patients. HIV positivity is still a poor prognostic factor in our setting, especially for patients not on HAART, on HAART for ≤ 10 months, or with a low CD4 count below 200 cells/mm3. Patients with HIV-HL were older and had higher LDH levels, whereas patients with non-HIV-HL were younger and had low LDH levels.